The influence of demographic variables to e-waste management practices in Kuala Lumpur, Malaysia - Tengku Adeline Adura Tengku Hamzah,; Amirah Sariyati Mohd Yahya,; Aziz Shafie, (Penerbit Universiti Kebangsaan Malaysia, 2022)
E-waste is defined as electrical and electronic appliances that are no longer functioning, broken, obsolete or unwanted by the present owner and are ready to be discarded. The disposal of e-waste is a challenging task as it contains hazardous substances as well as the precious metals. This study seeks to investigate e-waste management practices among respondents based on their demographic background. A quantitative cross-sectional study was conducted among 936 respondents in Kuala Lumpur, and questionnaires survey forms are used as research instrument. A statistical test was run to examine the relation of ten options of e-waste management practices to five demographic variables. The result has shown that respondents’ occupation is the most significantly related demographic variables to e-waste disposal practices compared to other demographic variables. Respondents that work in the private sector were reported to have the highest percentage for each e-waste disposal practices compared to other type of occupations. The factors that have led to this finding may be due to the working environment (which deals a lot with electrical and electronic appliances), as well as the exposure and information from wide range of sources. Overall, the e-waste disposal practices vary based on the demographic background. The output of this study is beneficial for decision makers and relevant agencies in creating an appropriate management actions and approach based on demographic background towards sustainable e-waste management in Malaysia.